Expression of calcitonin receptor-like receptor in human vascular tumours. - Hagner, Stefanie; Stahl, Ulrich; Grimm, T.; Stürzl, Michael; Lang, R. E. (Journal of Clinical Pathology, 2006)
Background: Vascular tumours such as Kaposi’s sarcoma and capillary haemangioma are characterised by abnormal vascularisation and proliferation of endothelial cells or neoplastic cells. Adrenomedullin, a potent vasodilative peptide, and its receptor, calcitonin receptor-like receptor (CRLR), play an important part in angiogenesis. Aim: To establish whether this system also plays a part in vascular diseases, showing abnormal proliferation such as vascular tumours. Methods: CRLR expression was investigated in several specimens of Kaposi’s sarcoma and other vascular tumours, using immunohistochemical analysis with a previously described CRLR-specific polyclonal antibody and reverse transcriptase-polymerase chain reaction. Results: Intense and specific CRLR-immunoreactive staining of neoplastic cells was observed in all specimens, which was of greater intensity than similar staining of adjacent normal endothelium. Conclusions: CRLR is expressed in vascular tumours and, with adrenomedullin, may have a role in neoplastic vascular growth.